SISTEM KOORDINASI ANTARA OTORITAS JASA KEUANGAN (OJK) DENGAN LEMBAGA PENJAMIN SIMPANAN (LPS) DALAM PENANGANAN BANK GAGAL - WIWIN WINTARSIH WINDIANTINA (Universitas Pamulang, 2016)
ABSTRACTThe banking industry is a dynamic sector along with economic growth, an increasing of complex financial transactions, and the impact from global trade, therefore the presence of an independent institutions is really needed. The Deposit Insurance Agency (LPS) is an institution that is independent, transparent and accountable in implementing its duties and authorities. As an independent agency, accountability is very important to be applied, so that stakeholders aware of what and how LPS implement the functions and duties as mandated by Law No. 24 of 2004 concerning the Deposit Insurance Agency (LPS). Procedurally, if the Financial Services Authority (OJK) indicate a bank that is experiencing liquidity problems, Financial Services Authority (OJK) immediately inform the Bank of Indonesia (BI) to take steps in accordance with BI's authority. In practise, Financial Service Authority (OJK) coordinate withBank of Indonesia (BI) to make regulatory supervision in banking sector. Coordination in handling between failed banks between the Deposit Insurance Agency (LPS) and Financial Services Authority (OJK) is shown by a confirmation from Financial Services Authority (OJK) to the Deposit Insurance Agency (LPS) about troubled banks that are in the restructuring efforts by Financial Services Authority (OJK), then the Deposit Insurance Agency (LPS) investigate the banks in accordance with its functions, duties and responsibilities. The Deposit Insurance Agency (LPS) as an institution that checks condition of banks surely will review and determine whether the troubled banks will be saved or not saved.